Collective bargaining and the flexibilisation of employment in Italy. (1st April 2010) - Alessia Vatta
Abstract : This paper compares the 1993 Accord between the Italian government and social partners with the 2009 Framework Agreement on the Reform of Collective Bargaining. The former was decisive for the institutionalisation of collective bargaining and the introduction of flexibility into the domestic labour market, while the latter has been more contestedm seeming to reflect increasing difficulties in the relationships between the main actors in Italian employment policy. The paper discusses the role of the different channels used to innovate work regulation in Italy, assesses the attitude of the actors involved, and suggests a possible direction for future policy initiatives.